2022
DOI: 10.3390/ma15072519
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graphene Oxide and Crumb Rubber on the Fresh Properties of Self-Compacting Engineered Cementitious Composite Using Response Surface Methodology

Abstract: Graphene oxide-modified rubberized engineered cementitious composite (GO-RECC) is attracting the attention of researchers because of the reported benefits of the GO and crumb rubber (CR) on the strength and deformation properties of the composite. While it is well established that GO negatively affects the workability of cementitious composites, its influence on the attainment of the desired self-compacting (SC) properties of ECC has not yet been thoroughly investigated, especially when combined with crumb rub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…As the viscosity rises, this stops the mixture from flowing. Abdulkadir et al [69] reported that the use of GO as a nano-additive component resulted in self-compacting ECC, which then resulted in reducing the slump flow of fresh concrete. According to Wei et al [70], the flow rate of cement matrixes comprising 0.01, 0.02, and 0.03% of GO, decreased by 7.9%, 10.0%, and 13.1%, respectively.…”
Section: Slump Flow Of Fresh Go-eccmentioning
confidence: 99%
“…As the viscosity rises, this stops the mixture from flowing. Abdulkadir et al [69] reported that the use of GO as a nano-additive component resulted in self-compacting ECC, which then resulted in reducing the slump flow of fresh concrete. According to Wei et al [70], the flow rate of cement matrixes comprising 0.01, 0.02, and 0.03% of GO, decreased by 7.9%, 10.0%, and 13.1%, respectively.…”
Section: Slump Flow Of Fresh Go-eccmentioning
confidence: 99%